Major Causes of Corruption in India and Problems of Indian Judicial System: Understanding the Challenges of Corruption in India and the Role of the Judicial System (Journal of Advances and Scholarly Researches in Allied Education, 2021)
“Without strong watchdog institutions, impunity becomes the very foundation upon which systems of corruption are built. And if impunity is not demolished, all efforts to bring an end to corruption are in vain.” Corruption in India itself is big issue or a challenge that each party has to face in order to establish good governance. Corruption is not easy to vanish as it has been a part and parcel of life style and way working of almost all the Indians. Actually the basic reason behind this malpractice is that now people are not afraid of any social stigma or criticism. Moreover the level of moral values and professional is zero now days. To combat with corruptions in India is like battling with a cancerous disease with no surety or security of recovery. This Article by the researcher is a sincere attempt with great honesty to highlight the major causes of corruption in India and the problems faced by Indian Judiciary in the way of eliminating corruption completely.